Assessment of the growing demographic threats to economic security in the regions of the North Caucasian Federal District - P. I. Bostanova; Z. Kh. Ozdoeva (Вестник университета)
The article is devoted to the study and assessment of demographic threats to the economic security of the regions of the North Caucasian Federal District. A brief overview of periodical publications covering pressing demographic challenges and their impact on economic security is provided. Methods of economic analysis were used as follows: generalization, absolute and relative value method, comparison, index and tabular methods, etc. To assess the threats, the authors used data collected by the Federal State Statistics Service, such as birth and death data, the rate of natural increase (decrease), and the rate of migration increase. The data on the population before and after the sharp aggravation of demographic problems caused by the spread of the coronavirus disease (COVID-19) were compared. An initial assessment of demographic processes that had jeopardized the economic security of the regions was made. Based on the analysis of the statistical data showing a change in the number of births and deaths in years 2019–2021, the authors point out a certain decrease in the birth rate and a dramatic increase in mortality, which caused a drop in the rate of natural increase up to negative values, in the federal district under study as a result of the pandemic. The decline in the intensity of migration flows was identified. The interdependence of the territory’s population decline trend and the able-bodied population decline trend was noted. A set of conclusions on the top demographic policy priorities of the state in the current realities were made, and the need to develop measures aimed at ensuring economic security in the demographic sphere was stressed.